Circulating levels of adropin and overweight/obesity: a systematic review and meta-analysis of observational studies - Soltani, Sepideh; Kolahdouz-Mohammadi, Roya; Aydin, Suleyman; Yosaee, Somaye; Clark, Cain C. T.; Abdollahi, Shima (Springer Int Publ Ag, 2022)
The association between circulating adropin levels and overweight/obesity is currently unclear. The aim of this study was thus to investigate and seek to determine the association between circulating adropin levels and overweight/obesity using the meta-analysis approach of observational studies. A comprehensive literature search was carried out through the PubMed, Web of Science, and SCOPUS databases to identify relevant observational studies that assessed the relationship between circulating adropin levels and overweight/obesity up to September 2020. A random-effects model was used to compute the pooled weighted mean difference (WMD) with 95% confidence intervals (CI). The meta-analysis of five studies (n = 643 participants) showed that circulating adropin levels were significantly lower in the overweight/obese vs. the normal-weight participants (WMD = - 0.96 ng/ml, 95% CI = - 1.72 to - 0.19, P = 0.01; I-2 = 88.4%). In subgroup analyses, lower circulating adropin levels in obese participants compared with normal-weight were observed in Asians (WMD = - 1.58 ng/ml, 95% CI = - 1.96 to - 1.21, P < 0.001; I-2 = 0.00%), and in patients with metabolic disorders (WMD = - 1.26 ng/ml, 95% CI = - 1.76 to - 0.77, P < 0.001; I-2 = 44.6%), respectively. Circulating adropin levels were significantly lower in overweight/obese vs. normal-weight participants, suggesting a possible role of this hormone in the development of obesity. However, the present research indicates that further studies are needed to conclusively confirm whether adropin is a viable marker of obesity.
Keywords: Adropin; Obesity; Meta-analysis; Overweight; Observational studies